Studies On Integrated Nutrient Management On Growth, Yield And Quality Of Carrot (Daucus Carota L.) Cv. Pusa Vasuda Under Valley Condition Of Garhwal Hills (Journal of Pharmaceutical Negative Results, 2022)
Integrated nutrient management has significant potential for addressing the increased nutritional demands of carrot cultivation and sustaining higher levels of yield with an overall improvement in the quality of the resource base. A well-balanced application of organic, inorganic, and biofertilizers is necessary to maintain a healthy soil (biological and chemical) environment and provide energy for the soil's microbial biomass. It contributes to enhancing and maintaining soil fertility and provides a solid foundation for horticultural production systems that can adapt to changing conditions. This study aimed to investigate the interaction effects of organic (FYM & Chicken Manure), inorganic (RDF 100%) & Biofertilizer (Azotobacter & Azospirillum) on growth, yield, and quality of carrot (Daucus carota L.) Cv. Pusa Vasuda under valley condition of Garhwal hills during the rabi season, 2016-2017 at Horticultural Research Centre, Department of Horticulture, H.N.B. Garhwal University, Srinagar Garhwal, (Uttarakhand), India. A randomized block design was used for the experiment, which was replicated thrice comprising 20 treatments [Control (non-amended soil) + 19 (treatments and their combination). The experiment was conducted with two main objectives, i.e., to find out the effect of different inorganic, organic, and bio-fertilizers and their combination and to assess the best nutrients for growth, yield, and quality of carrot. The results indicated that the treatment T14 [RDF (100%) + Azospirillum] was rated as best for the growth parameter like minimum days to first seed germination (13.33 days), plant height at 60 DAS (31.44cm), number of leaves after 60 DAS (7.44) and leaves weight (62.38 g) in carrot. However, yield parameters like maximum core diameter (1.20 cm), cortex diameter (1.47 cm), and root diameter (2.67 cm) were observed in treatment T16 [FYM + RDF (100%) + Azotobacter], while root weight (175.03 g) was observed in treatment T1 (FYM). On the other hand, quality parameter like vitamin-A (8222.67 I.U./100g) was recorded in treatment T12 (Chicken manure + Azospirillum), total soluble solid (9.00 o Brix) in treatment T16 (FYM + 100% RDF + Azotobacter) and vitamin C (7.26 mg/100g) in treatment T5 (Azospirillum). Based on the results of the above investigation, Pusa Vasuda responded well to the treatment T14 [RDF (100%) + Azospirillum] and T16 [FYM + RDF (100%) + Azotobacter] for various growth and yield parameters. Hence, these treatments could be recommended to enhance carrot production under Garhwal hills.